Impact of Submarine Groundwater Discharge on Microbial Communities in a Highly Anthropized Coastal Lagoon (Mar Menor, SE Spain) - Daniel Romano‐Gude; Júlia Dordal‐Soriano; Júlia Rodriguez‐Puig; Andrea G. Bravo; Irene Alorda‐Montiel; Aaron Alorda‐Kleinglass; Marc Diego‐Feliu; Cristina Romera‐Castillo; Rebeca Mallenco‐Fornies; Javier Gilabert; Jordi Garcia‐Orellana; Valentí Rodellas; et al. (Molecular Ecology, 2025)
Submarine groundwater discharge (SGD) supplies large quantities of nutrients and other terrestrial elements to coastal ecosystems, impacting marine biota and ecosystem functioning. Despite the relevance of prokaryotes for marine biogeochemistry, little is known about their responses to groundwater inputs. Here we explored the impact of SGD on the spatiotemporal patterns of prokaryotic communities from the Mar Menor (Murcia, Spain), a highly anthropized hypersaline coastal lagoon that receives large amounts of nutrient‐polluted SGD. Using 16S rRNA amplicon sequencing, activity assays, and flow cytometry, we investigated the dynamics of prokaryotic communities across the lagoon and its connected environments (freshwater streams, groundwater, soils, the sea) on two occasions. We found that the lagoon areas most influenced by SGD (i.e., sites closest to the shore) presented on average three‐fold higher heterotrophic prokaryotic protein production than the inner lagoon samples, and 2.7‐fold higher taxonomic richness. This spatial pattern was likely influenced by solutes supplied by SGD, as higher concentrations of dissolved nitrogen, silicate and SGD tracers (radium [Ra] isotopes) were found in nearshore waters. Increases in these elements also influenced the relative abundance of dominant bacterial groups (e.g., Flavobacteriales, Rhodobacterales). In autumn, increases in lagoon 224 Ra were strongly linked to higher taxonomic richness in microbial assemblages and the influx of allochthonous taxa from the catchment, pointing to seasonally variable transport of coastal groundwater microorganisms via SGD. Our study highlights SGD as an overlooked driver of prokaryotic dynamics in coastal ecosystems, and suggests that changes in this process may significantly impact microbial community structure and functioning.